The RISOTTO radiative transfer and retrieval pipeline for the analysis of occultation spectra. (November 2021) - Braude, A.S.; Ferron, S.; Montmessin, F.
Highlights: New radiative transfer and retrieval pipeline designed for occultation data. Able to correct for uncertainties in multiple instrumental parameters. Results validated to be within 2% of existing radiative transfer codes. Abstract: We present a new radiative transfer and retrieval pipeline, referred to as RISOTTO, designed for observations made in occultation geometry. RISOTTO can retrieve accurate vertical profiles of the constituents of a planetary atmosphere using a Bayesian approach while simultaneously correcting for instrumental artefacts and uncertainties. The algorithm makes use of a rapid Abel integration scheme involving matrix multiplication, using pre-calculated gaseous cross-section data to calculate the integration along the line of sight, while also separating out any effects of transmission baseline variation. We assess its accuracy using synthetic solar occultation spectra of Mars and comparing it with the older more established NEMESIS radiative transfer and retrieval pipeline (Irwin et al. 2008, J. Quant. Spec. Radiat. Transf. 109, 1136–1150), and show that it can match its accuracy while also being able to more easily retrieve gases with substantial continuum absorption.